2015
DOI: 10.20510/ukjpb/3/i3/89384
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Estimation of Plumbagin in Aerial and Root Part of Plumbago zeylanica Using UV-Visible Spectrophotometric

Abstract: Plumbago zeylanicais one such important medicinal plant which is being used the world over in the traditional system of medicines. The plant is being used extensively in commercial preparations of medicines. The plumbagin present in different parts of Plumbago zeylanica as active constituent and it imparts wide range of biological activities. In the present study we planned to check the concentration of plumbagin present in aerial and root of Plumbago zeylanica. The petroleum ether, ethanol and aqueous extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…In recent years, the functional genomics approach supported by targetedmetabolite and transcriptome profiling has been widely used as an efficient tool for deciphering novel gene functions in phytomedicine. 18 Owing to the rapid boom in cost effective high-throughput next generation sequencing technologies, a hot quest for sequencing the genomes and transcriptome of these life-saving medicinal plants have been instigated recently. 19 Nevertheless, large-scale bio prospection approaches in genomics and transcriptomics of phytomedicine is still its underway for exploring novel potentially important plant species.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the functional genomics approach supported by targetedmetabolite and transcriptome profiling has been widely used as an efficient tool for deciphering novel gene functions in phytomedicine. 18 Owing to the rapid boom in cost effective high-throughput next generation sequencing technologies, a hot quest for sequencing the genomes and transcriptome of these life-saving medicinal plants have been instigated recently. 19 Nevertheless, large-scale bio prospection approaches in genomics and transcriptomics of phytomedicine is still its underway for exploring novel potentially important plant species.…”
Section: Discussionmentioning
confidence: 99%
“…There are three species in the genus Plumbago, namely Plumbago indica L./ P. Rosea L., P. capensis L., and P. zeylanica L., which are spread across India. In India, Pz grows as a wild species in various parts but is also cultivated because of its large therapeutic applications 12,15 . There is no consensus in the literature citing Pz as being listed as herb or shrub.…”
Section: Botanymentioning
confidence: 99%
“…The GC-MS analysis of Pz revealed the presence of 40 compounds that could contribute to the medicinal property of the plant 5 . Different parts of the plant possess alkaloids, carbohydrates, triterpenoids, flavonoids, gums, mucilage, protein, fatty acids, saponin, 8,28 plumbagin, plumbagic acid, chitanone, plumbaginol, dihydroflavinol, campesterol, stigmasterol, sitosterol, glucopyranoside, sitosterol, 29 naphthoquinones, glycosides, steroids, tannins, phenolic compounds and coumarins 15,30 .…”
Section: Chemical Constituentmentioning
confidence: 99%
See 1 more Smart Citation
“…Plumbagin is also reported to be produced by various plant genera belongs to other botanical families viz. Droseraceae and Ebenaceae etc (Padhye et al 2012) but the members of the family Plumbaginaceae reported to produce plumbagin at high concentration with maximum (1.0% of the dry weight) by P. zeylanica (Dohare et al 2015). As per reports (Paiva et al 2003; Sinha et al 2013), plumbagin is having anticancer, antibacterial and antifungal activities (Aziz et al 2008).…”
Section: Introductionmentioning
confidence: 99%